ICTV Virus Taxonomy Profile: Yadokariviridae 2023. (27th January 2023) - Sato, Yukiyo; Das, Subha; Velasco, Leonardo; Turina, Massimo; Osaki, Hideki; Kotta-Loizou, Ioly; Coutts, Robert H. A.; Kondo, Hideki; Sabanadzovic, Sead; Suzuki, Nobuhiro; ,
Abstract : The family Yadokariviridae, with the genera Alphayadokarivirus and Betayadokarivirus, includes capsidless non-segmented positive-sense (+) RNA viruses that hijack capsids from phylogenetically distant double-stranded RNA viruses. Yadokarivirids likely replicate inside the hijacked heterocapsids using their own RNA-directed RNA polymerase, mimicking dsRNA viruses despite their phylogenetic placement in a (+) RNA virus lineage. Yadokarivirids can have negative or positive impacts on their host fungi, through interactions with the capsid donor dsRNA viruses. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) report on the family Yadokariviridae, which is available at ictv.global/report/yadokariviridae .